2010
DOI: 10.1097/lgt.0b013e3181a911b8
|View full text |Cite
|
Sign up to set email alerts
|

The Optimum Organization for the Delivery of Colposcopy Service in Ontario

Abstract: Overall, the Ontario Colposcopy Guidelines Development Group believes that the benefits associated with the implementation of colposcopy recommendations in Ontario will result in greater organization of care and improved patient outcomes. In addition, the group anticipates that these recommendations will provide useful guidance to regional planning authorities, hospital administrators, and Cancer Care Ontario, as well as colposcopists and other practitioners, in the planning of integrated regional and provinci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…Many organisations have developed strategies to reduce default from colposcopy services (14,16,18). However, a large postal survey in the UK found that default was hard to predict using standard demographic variables, although an intention to attend the clinical service three weeks before the appointment date was associated with a higher rate of attendance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many organisations have developed strategies to reduce default from colposcopy services (14,16,18). However, a large postal survey in the UK found that default was hard to predict using standard demographic variables, although an intention to attend the clinical service three weeks before the appointment date was associated with a higher rate of attendance.…”
Section: Discussionmentioning
confidence: 99%
“…Other organisations have used evidence-based guidelines to develop service protocols designed to improve care outcomes and minimise default (18). These processes have not relied upon close examination of the individual features and social circumstances of the attending patients.…”
Section: Discussionmentioning
confidence: 99%
“…This "guideline of guidelines" approach is the same that used in the 2008 cco evidence-based series 15-12 document, The Optimum Organization for the Delivery of Colposcopy Service in Ontario 11 . The "guideline of guidelines" approach is a practical way to generate consensus and expert opinion-based recommendations to establish best practices within Ontario; however, it has some drawbacks.…”
Section: Discussion and Cervical Cancer Screening Clinical Advisory Cmentioning
confidence: 99%
“…The members of the Working Group endorse the accessibility to training programs, the training and qualification requirements, and the program scope recommendations contained in the 2008 cco guideline 11 . The recommendations for maintenance of competence represent the consensus of the Working Group members based on guidance provided by the nhscsp in the United Kingdom 3 , the ranzcog in conjunction with the asccp Working Party 4 , and the 2008 cco guideline 11 .…”
Section: Justificationmentioning
confidence: 99%
See 1 more Smart Citation